SYARAT PERLU DAN SYARAT CUKUP KEBERADAAN DAN KETUNGGALAN KESEIMBANGAN NASH CAMPURAN SEMPURNA PADA BIMATRIX GAMES - Anggi Mutia Sani (Jurnal Matematika UNAND, 2013)
In this paper, the necessary and sucient condition for the existence anduniqueness of a completely mixed Nash equilibrium in bimatrix games [A;AT ] are pre-sented. Matrix A 2 Rnn is a payo matrix. The necessary and sucient condition areexpressed with some properties of saddle point matrices, denoted by (A; e), where e isthe column vector with all entries 1. Properties of the saddle point matrices assessedusing the algebraic approach.